Biosynthesis of silver nanoparticles using Tamarix articulata leaf extract: an effective approach for attenuation of oxidative stress mediated diseases. Issue 1 (1st January 2021) - Anwar, Shehwaz; A. Almatroodi, Saleh; Almatroudi, Ahmad; Allemailem, Khaled S.; Joseph, Rejo Jacob; Khan, Amjad Ali; Alrumaihi, Faris; Alsahli, Mohammed A.; Husain Rahmani, Arshad
ABSTRACT: To investigate the biosynthesis of silver nanoparticles (T-AgNPs) using leaf extract of Tamarix articulata and their possible role in attenuation of oxidative stress mediated human diseases. T-AgNPs were characterized by several biophysical techniques. Various health beneficial activities were also investigated. The synthesized T-AgNPs showed an absorption peak at 413 nm on UV-Visible spectroscopy indicating the surface plasmon resonance of the nanoparticles. TEM analysis clearly showed that particles were spherical with an average size of about 25 nm. SEM image analysis confirmed the spherical shape of T-AgNPs. T-AgNPs (600 µg/ml) showed effective DPPH scavenging (68.23%), ferric reducing (68.23%), and hydrogen peroxide reducing (70.09%) activities. Besides, T-AgNPs at 600 µg/ml, also showed strong anti-glycating, and AGEs formation inhibitory activities as indicated by reduced browning intensity (51.62%), aggregation index (48.86%), and cross amyloid structures (53.62%) as compared to positive controls (100%). A 600 µg/ml of T-AgNPs was found to have potent in vitro anti-inflammatory activity as revealed by albumin denaturation inhibition (73.19%), protease activity inhibition (70.196%), membrane stability against heat (74.16%), and hyposaline (72.98%) induced hemolysis as compared to controls. Altogether, these findings confirm that T-AgNPs can be promising candidates for the development of antioxidant, anti-inflammatory, membrane stabilizing, antiglycating and AGEs inhibitory agents.